PERFORMANCE OF FAT-TAILED RAMS FED COMPLETE FEED BASED OIL PALM FRONDS - Hamidah, A.; Sutrisno, C.I.; Sunarso, S.; Christiyanto, M.; Nuswantara, L.K.; Muthalib, R.A. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The aim of this experiment was to evaluate the performance of fat-tailed rams fed complete feedbased oil palm fronds (OPF). This experiment was arranged in Completely Randomized Design (CRD)with 5 treatments and 4 replications i.e. 0, 25, 50, 75 and 100% of OPF substituting fields grass incomplete feed for A, B, C, D and E treatments, respectively. Twenty fat-tailed rams were fed twice at08.00 and 14.00 with pellet of complete feed for 4 months. The result of this experiment showed thatOPF significantly influenced nutrient consumption, average daily gain (ADG) and feed efficiency ratio(FER). Oil palm fronds significantly affected (P<0.05) fat-tailed rams’s dry matter intake (DMI), organicmatter intake (OMI), crude protein intake (CPI), ADG and FER. The highest DMI, OMI, CPI, ADG, andFER of fat-tailed rams was in C treatment and significantly different from the others. It was concludedthat C treatment was the best treatment which can give the best fat-tailed rams performance. The OPFcan be used to replace the field grass as feed up to 75% proportion in complete feed and could increasethe performance and productivity of fat-tailed rams.